2010
DOI: 10.1161/circimaging.109.931592
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Resistance, Collateral Flow, and Ventricular Function in Patients With a Fontan Circulation at Rest and During Dobutamine Stress

Abstract: Background-The role, interplay, and relative importance of the multifactorial hemodynamic and myocardial mechanisms causing dysfunction of the Fontan circulation remain incompletely understood. Methods and Results-Using an MRI catheterization technique, we performed a differential analysis of pulmonary vascular resistance and aortopulmonary collateral blood flow in conjunction with global ventricular pump function, myocontractility (end-systolic pressure-volume relation), and diastolic compliance (end-diastoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 46 publications
5
53
0
1
Order By: Relevance
“…The pulmonary vascular resistance (PVR) was calculated using the invasive pressure data and the CMR flows as the quotient between transpulmonary gradient and effective antegrade pulmonary flow defined as the sum of antegrade flow as measured in SVC and IVC plus collateral blood flow [8,10]. The transpulmonary gradient was calculated as the difference between mean pulmonary artery pressure and pulmonary capillary wedge pressure.…”
Section: Cardiovascular Magnetic Resonance Imaging (Cmr)mentioning
confidence: 99%
See 2 more Smart Citations
“…The pulmonary vascular resistance (PVR) was calculated using the invasive pressure data and the CMR flows as the quotient between transpulmonary gradient and effective antegrade pulmonary flow defined as the sum of antegrade flow as measured in SVC and IVC plus collateral blood flow [8,10]. The transpulmonary gradient was calculated as the difference between mean pulmonary artery pressure and pulmonary capillary wedge pressure.…”
Section: Cardiovascular Magnetic Resonance Imaging (Cmr)mentioning
confidence: 99%
“…The observed inverse relationship between APC flow and vascular resistance indicates that additional pulsatile flow through APCs into the pulmonary vasculature seems not to increase, but even lowers pulmonary vascular resistance [10]. However, it has to be kept in mind that the mean follow-up after Fontan procedure was below 10 years and the long-term effect of these collaterals on the structure and remodelling of the distal pulmonary vascular bed remains unknown.…”
Section: Effect Of Apc Flow On Pulmonary Vascular Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors' data indicate that pulmonary vascular response to augmented cardiac output was adequate, but decreased diastolic compliance was identified as an important component of ventricular dysfunction. 10 Editor's Comment: Please refer to the comment following article In addition, this collateral flow was on average more than half of the total pulmonary blood flow and more than one third of the cardiac output (aortic flow), and ventricular end-diastolic volume correlated with collateral flow. This suggests that collateral flow can be a significant hemodynamic burden in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Geva et al evaluated cardiac function after surgery for TOF in patients by using MRI and reported the risk factors [14]. Schmitt evaluated cardiac function during exertion after the Fontan procedure in patients by using MRI [15]. As shown in the abovementioned and many other studies, cine MRI is used more often in the evaluation of cardiac function than is any other technique in cases of CHD [16,17].…”
Section: Analysis Of Cardiac Functionmentioning
confidence: 99%